Multilayer Transmissions of Spoof Surface Plasmon Polaritons for Multifunctional Applications. Issue 1 (3rd November 2016) - Pan, Bai Cao; Zhang, Hao Chi; Cui, Tie Jun
Abstract : Multilayer transmissions of spoof surface plasmon polaritons (SSPPs) with high isolations among the multiple channels are presented. For this purpose, a novel SSPP structure that consists of a metallic strip line and a corrugated metallic strip line is proposed, which brings in a solution to overcome the strong coupling of conventional SSPP structures in multiple‐layer applications. Very good isolation properties between two overlapped SSPP waveguides are achieved. More importantly, the property of isolation or coupling between the two overlapped waveguides can be switched by tuning the opening direction of the corrugation grooves. Each channel of the multilayer SSPP system operates independently, making it possible to realize the multilayer multiple‐functional SSPP devices. A prototype of double‐functional device is designed and fabricated, in which two different frequency rejections are achieved in two channels, respectively, without any mutual couplings. Experimental results agree well with the numerical simulations. The proposed design illustrates great potentials in modern plasmonic integrated circuits, opening new vistas in much more complicated multiple‐layer plasmonic systems. Abstract : Multilayer transmissions of spoof surface plasmon polaritons (SSPPs) are presented with high isolations among the multiple channels based on a novel SSPP structure. The transmission line can be switched between the coupling state and isolated state. Under the isolated state, each channel of the multilayer SSPP system operates independently, making it possible to realize the multilayer multiple‐functional SSPP devices.